Prevalence of Hepatitis B, C, and D in Germany: Results From a Scoping Review - Sperle, Ida; Steffen, Gyde; Leendertz, Siv Aina; Sarma, Navina; Beermann, Sandra; Thamm, Roma; Simeonova, Yanita; Cornberg, Markus; Wedemeyer, Heiner; Bremer, Viviane; Zimmermann, Ruth; Dudareva, Sandra (Frontiers in Public Health, 2020)
Background: One of the five strategic directions in the World Health Organization global health sector strategy on viral hepatitis 2016-2021 is to generate strong strategic information for focused action to understand the viral hepatitis epidemic and focus the response. Knowledge of national prevalence is a cornerstone of strategic information. Germany is considered to be a low prevalence country for viral hepatitis B, C and D, however the prevalence is likely to be higher among at-risk groups. Methods: The aim of this work was to give a detailed overview of the prevalence of viral hepatitis B (HBsAg, anti-HBc), C (anti-HCV, HCV RNA) and D (anti-HDV, HDV RNA) in different population groups in Germany. Therefore, we analysed the results of a comprehensive literature search on various aspects of the epidemiological situation of hepatitis B, C and D in Germany. Eligible publications including information on hepatitis B, C and D prevalence were extracted from the overall spreadsheet table and summarized and analyzed based on virus and different population groups. A quality appraisal was performed using a checklist developed by Hoy et al. to assess risk of bias in prevalence studies. Results: Overall, 51 publications were identified through the literature search. The overall prevalence of HBsAg in the general (and proxy) population ranged from 0.3-1.6%. Among at- risk groups, including clinical populations and health care workers, the HBsAg prevalence ranged from 0.2% (among rheumatic patients) to 4.5% among HIV positive patients. The overall prevalence of anti-HCV in the general (and proxy) population ranged from 0.2-1.9%. Among at risk groups, including clinical populations and health care workers, the anti-HCV prevalence ranged from 0.04% (among health care workers) to 68.0% among people who inject drugs. Conclusions: The hepatitis B and C prevalence in the general population in Germany is low. Prevalence is high to very high among at-risk populations, however for some groups evidence was incomplete or missing completely. To reach the elimination goals in Germany and implement a targeted response, more research among at-risk groups is needed.